O instagram do shopping Iguatemi de Porto Alegre no distanciamento social da COVID-19 : de vitrine on-line para revista de moda - Albrecht, Regina Martins (2023)
This research seeks to understand the transformation of communication adopted by companies focused on fashion retail due to social distancing in the Covid-19 pandemic. For this, communication via social networks was chosen, with Instagram as the environment. As a corpus, the profile of Shopping Iguatemi in Porto Alegre, the first mall in the southern region of Brazil, will be worked on. Through Content Analysis (BARDIN, 2011), the months from January to May 2020 and January to May 2022 are studied, which the author calls pre and post social isolation periods. It is noted that the profile underwent a change in its content in the quest to expand social ties (RECUERO, 2018) with the public, even when the mall was closed due to social distancing. For the study, authors such as Canclini (1997) and Fontenelle (2017) are used to talk about consumption, Chiavenato (2003) about technology and even Pellanda (2005, 2009), Primo (2003, 2007) and Santaella (2016) lecturing about mobile internet, interactivity and cyberspace. It was seen that one of the strategies of Shopping Iguatemi in Porto Alegre to transform its content on Instagram was to appropriate what was already happening in physical environments, moving from “great temples of consumption” to “great temples of experiences"